Improvement in insulin sensitivity and serum leptin concentration after the switch from a ritonavir-boosted PI to raltegravir or dolutegravir in non-diabetic HIV-infected patients. (12th December 2018) - Calza, Leonardo; Colangeli, Vincenzo; Borderi, Marco; Coladonato, Simona; Tazza, Beatrice; Bon, Isabella; Re, Maria Carla; Viale, Pierluigi
Abstract: Objectives: An observational, prospective, cohort study was performed to assess changes in insulin sensitivity and serum leptin level after a switch from a ritonavir-boosted PI (PI/r) to raltegravir or dolutegravir in HIV-infected adults on stable combination ART (cART). Methods: Non-diabetic HIV-infected patients receiving suppressive cART including tenofovir disoproxil fumarate/emtricitabine plus one PI/r, who underwent a switch from the PI/r to raltegravir (group A) or dolutegravir (group B), were enrolled in the study. Serum levels of insulin, leptin and the homeostasis model assessment of insulin resistance (HOMA) index were evaluated during a 12 month follow-up. Results: Overall, 86 patients were enrolled: 45 patients were included in group A and 41 were included in group B. The mean age was 45.7 years and 74 (86%) patients were male. After 12 months of follow-up, a significant reduction in the mean concentration of leptin and insulin was reported both in group A [−0.61 ng/mL ( P <  0.001) and −2.5 mIU/L ( P =  0.008), respectively] and in group B [−0.54 ng/mL ( P =  0.005) and −2.1 mIU/L ( P =  0.017), respectively], without a significant difference between the groups. A significant and comparable reduction in the mean HOMA index was reported both in group A [−0.55 ( P =  0.004)] and in group B [−0.49 ( P <  0.001)], as well as a significant decrease in lipid levels. Conclusions: In HIV-positive subjects on suppressive cART, the switch from a PI/r to raltegravir or dolutegravir led to a significant and comparable reduction in both HOMA index and serum leptin level, reflecting a similar and significant improvement in insulin sensitivity.